Experimental Study on Module-to-Module Thermal Runaway-Propagation in a Battery Pack. Issue 10 (1st January 2019) - Gao, Shang; Lu, Languang; Ouyang, Minggao; Duan, Yongkang; Zhu, Xinwei; Xu, Chengshan; Ng, Benjamin; Kamyab, Niloofar; White, Ralph E.; Coman, Paul T.
Abstract : An experimental study of the module-to-module thermal runaway (TR) propagation in a multi-modular battery pack is presented here. During the experiment a cell in one of the modules is triggered by heating to study both cell-to-cell and module-to-module propagation. In order to understand the mechanism and gain insight into the thermal hazards of a battery pack system, the thermal characteristics of the cells in different modules are analyzed in detail. Although the TR-propagations are all triggered from the side next to the heater, the results indicate that the thermal characteristics of the modules vary in different phases. The upward direction of burning flame and heat flow highlight the importance of design considerations in a multi-modular battery pack.